ABOUT ARCHAEOLOGICAL SURVEY IN TASHKENT REGION (2022)* - Özlem, Jale; Murodaliev, Rakhmonali; Askarov, Ollabergan (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The article describes archaeological research conducted in 2022 in the Bostanlyk district of the Tashkent region and the results obtained from it. It is especially noteworthy that in the upper reaches of the Paltau River, researchers discovered graves belonging to ancient nomads. This indicates that cattle-breeding tribes have mastered the northern parts of the Tashkent oasis since the Bronze Age.